New Technology and New Roles: The Need for 'Corpus Editors' - Crane, Gregory; Rydberg-Cox, Jeffrey A. (Tufts Archival Research Center, 2005)
Digital libraries challenge humanists and other academics to rethink the relationship between technology and their work. At the Perseus Project, we have seen the rise of a new combination of skills. The "Corpus Editor" manages a collection of materials that are thematically coherent and focused but are too large to be managed solely with the labor-intensive techniques of traditional editing. The corpus editor must possess a degree of domain specific knowledge and technical expertise that virtually no established graduate training provides. This new position poses a challenge to humanists as they train and support members of the field pursuing new, but necessary tasks.